2019
DOI: 10.1016/j.cub.2019.05.058
|View full text |Cite|
|
Sign up to set email alerts
|

Reconstitution of Microtubule Nucleation In Vitro Reveals Novel Roles for Mzt1

Abstract: Summary Microtubule (MT) nucleation depends on the γ-tubulin complex (γ-TuC), in which multiple copies of the heterotetrameric γ-tubulin small complex (γ-TuSC) associate to form a ring-like structure (in metazoans, γ-tubulin ring complex; γ-TuRC) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Additional conserved regulators of the γ-TuC include the small pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 58 publications
3
31
0
Order By: Relevance
“…Figure 1C). In a recent density-gradient centrifugation analysis, Mto1/2[bonsai] sedimented with a peak at 9-10S and a very long "tail", extending to 20S and beyond, suggesting that the complex forms higher-order multimers (Leong et al, 2019). Consistent with this, using size-exclusion chromatography with multi-angle light scattering (SEC-MALS) we found that the Mto1/2[bonsai] SEC peak comprises a range of molecular masses (Suppl.…”
Section: Both Mto1/2[bonsai] Complex and Mto2 Form Higher-order Multisupporting
confidence: 75%
See 4 more Smart Citations
“…Figure 1C). In a recent density-gradient centrifugation analysis, Mto1/2[bonsai] sedimented with a peak at 9-10S and a very long "tail", extending to 20S and beyond, suggesting that the complex forms higher-order multimers (Leong et al, 2019). Consistent with this, using size-exclusion chromatography with multi-angle light scattering (SEC-MALS) we found that the Mto1/2[bonsai] SEC peak comprises a range of molecular masses (Suppl.…”
Section: Both Mto1/2[bonsai] Complex and Mto2 Form Higher-order Multisupporting
confidence: 75%
“…In this work we provide insights into assembly and architecture of the Mto1/2 microtubule nucleation complex, through biophysical and structural analysis of the Mto1/2[bonsai] complex, a freely-diffusible, minimal form of the Mto1/2 complex that retains Mto1/2's ability to promote g-tubulin complex-dependent microtubule nucleation (Leong et al, 2019;Lynch et al, 2014). Previous imaging of Mto1/2[bonsai] puncta in vivo suggested that higher-order structure and stability of Mto1/2[bonsai] complex may depend on underlying multimerization of Mto2, as well as additional cooperative interactions (Lynch et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations